Catalytic Core of Alphavirus Nonstructural Protein nsP4 Possesses Terminal Adenylyltransferase Activity - Tomar, Shailly (American Society for Microbiology, 2006)
The RNA-dependent RNA polymerase nsP4 is an integral part of the alphavirus replication complex. To define the role of nsP4 in viral RNA replication and for a structure-function analysis, we expressed Sindbis virus nsP4 in Escherichia coli. The core catalytic domain of nsP4 (Δ97nsP4, a deletion of the N-terminal 97 amino acids), which consists of the predicted polymerase domain containing the GDD amino acid motif required for viral RNA synthesis, was stable against proteolytic degradation during expression. Therefore, the recombinant core domain and selected mutants were expressed and purified to homogeneity. We determined that Δ97nsP4 possesses terminal adenylyltransferase (TATase) activity, as it specifically catalyzed the addition of adenine to the 3′ end of an acceptor RNA in the presence of divalent cations. Furthermore, Δ97nsP4 is unable to transfer other nucleotides (UTP, CTP, GTP, and dATP) to the acceptor RNA in the absence or presence of other nucleotides. Δ97nsP4 possessing a GDD-to-GAA mutation completely inactivates the enzymatic activity. However, a GDD-to-SNN mutation did not inactivate the enzyme but reduced its activity to ∼45% of that of the wild type in the presence of Mg(2+). Investigation of the TATase of the GDD-to-SNN mutant revealed that it had TATase equivalent to that of the wild type in the presence of Mn(2+). Identification of Δ97nsP4 TATase activity suggests a novel function of the alphavirus RNA-dependent RNA polymerase in the maintenance and repair of the poly(A) tail, an element required for replication of the viral genome.